ORIENTALISM AND RESISTANCE IN TJERITA NJI PAINA BY H.F.R. KOMMER - Hasina Fajrin; Muhammad Hasby; Nurmy AR (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
Tjerita Nyi Paina is one of the works published before the Balai Pustaka era. This work is interesting to discuss using orientalism because it illustrates the colonial era so that the nuances of colonialism are still very much felt and illustrate the discourse of East produced by the West and how the authors as Chinese descendants who occupy the second class describe the discourse on East and West. After being analyzed, Tjerita Nji Paina portrays that the West is higher than the East much of the story of Nji Paina, although eventually the Toean Briot hegemony was broken down through Nji Paina's resistance. Nji Paina's actions that seemed unreasonable to the West were what the West feared, so they then formed a discourse about the East to create hegemony. In addition, domination also seems to occur because this short story is still set in the colonial period, although not too highlighted the tortures carried out by the colonialists. This may be due to the fact that those who wrote were Chinese and the Chinese community, when the racial segregation carried out by the colonizers; they occupied a higher position than the natives.